Online Course Evaluation for the Development of Research Competences under a Socio-constructivist Pedagogical Approach - Ríos Cabrera, Pablo (2023)
The results of the evaluation of an online course are presented to develop investigative skills under a socio-constructivist pedagogical approach. Eleven subjects of both genders, university professionals from Latin America, and members of a cohort of the International Diploma in Investigative Competences participated in the course. Moreover, a mixed research design was used. For the quantitative analysis, a self-assessment scale (pretest and posttest) was used, which served to measure the acquisition of investigative skills. For the qualitative analysis, the focus group, a self-assessment rubric, and a final evaluation questionnaire of the course were used. The results indicate that there were statistically significant differences between the pretest and posttest of investigative skills (p < .001). 73% of the participants consider that they fully achieved the investigative competencies, while 27% partially achieved them and there were no participants in the not achieved category. In addition, the participants reached their achievement expectations in 90.6% of the cases and 63.6% of the individuals exceeded their achievement expectations. Therefore, it is concluded that the socio-constructivist pedagogical approach used was effective and efficient in the development of investigative skills, so its use in teaching research at the university is highly recommended. This research highlights the importance of the mediating work of teachers in the integration of research theory and practice, as well as the use of digital technologies to achieve active and collaborative learning. Thus, this study offers an innovative pedagogical perspective for the teaching of research at the university. However, the small sample size is recognized as a limitation. Hence, it is suggested that in future research the study be extended to a greater number of participants in different university contexts.